A Macro-meso damage coupling rock mass damage model based on improved internal crack analysis - Haian Liang; Miao He; Hongliang Zhao; Yiru Zhang; Qingrui Lu; Shuren Hao; Zhiying Gong; Hao Guan (PLoS ONE, 2025)
The complex geological genesis and different geological environments of rocks can lead to defects such as micropores, microcracks, and joints, resulting in the degradation of their engineering mechanical properties. In order to describe the deformation and failure mechanisms of jointed rock, a rock damage constitutive model that accounts for the geometric parameters and mechanical properties of internal joints within the rock is proposed. By leveraging the principles of damage mechanics and the Lemaitre strain equivalence hypothesis, macroscopic and microscopic damages in rock were combined, ultimately resulting in the development of a damage constitutive model that encompassed both scales of damage. The damage constitutive model was verified by uniaxial compression tests of clay-like rock under different joint dip angles and joint area combinations. The results indicated that the proposed damage constitutive model had clear physical significance and could fully reflect the process of rock failure, which was highly consistent with experimental results. The model parameter m reflected the brittleness of jointed rocks, while F₀ reflected the average strength of jointed rocks. The combination of macroscopic and microscopic analysis methods used in this study is reasonable, and the established damage constitutive model reflects the mechanical behavior of rocks and fits the experimental results well.